2018
DOI: 10.3389/fmicb.2018.01207
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility of Escherichia coli and Salmonella spp. Isolates From Healthy Pigs in Australia: Results of a Pilot National Survey

Abstract: This study investigated the frequency of antimicrobial non-susceptibility (defined as the frequency of isolates with minimum inhibitory concentrations above the CLSI susceptible clinical breakpoint) among E. coli and Salmonella spp. isolated from healthy Australian finisher pigs. E. coli (n = 201) and Salmonella spp. (n = 69) were isolated from cecal contents of slaughter-age pigs, originating from 19 farms distributed throughout Australia during July-December 2015. Isolates underwent minimum inhibitory concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
41
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 32 publications
11
41
1
1
Order By: Relevance
“…According to literature studies, our data differ to other regions of the world. In a study in 2018 on commensal E. coli isolates from healthy slaughter pigs in Australia, frequencies of resistant isolates (ampicillin~60.2%, tetracycline 68.2%, ciprofloxacin 1%, gentamicin and ceftiofur 0%) were lower than in our German sampling [38], which is mainly due to the fact that only healthy slaughter pigs were sampled in this previous study. A recent study in Estonia revealed lower percentages of tetracyclineresistant E. coli isolates in healthy swine (32.5%) compared to diseased swine (60.2%) as well [39].…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…According to literature studies, our data differ to other regions of the world. In a study in 2018 on commensal E. coli isolates from healthy slaughter pigs in Australia, frequencies of resistant isolates (ampicillin~60.2%, tetracycline 68.2%, ciprofloxacin 1%, gentamicin and ceftiofur 0%) were lower than in our German sampling [38], which is mainly due to the fact that only healthy slaughter pigs were sampled in this previous study. A recent study in Estonia revealed lower percentages of tetracyclineresistant E. coli isolates in healthy swine (32.5%) compared to diseased swine (60.2%) as well [39].…”
Section: Discussioncontrasting
confidence: 72%
“…Recently, a positive relationship between oral administration of chlortetracycline in nursery pigs and the probability of occurrence of E. coli isolates resistant to chlortetracycline and ceftiofur has been described [46]. In Australia, the very low level of non-susceptibility to critically important antimicrobials such as thirdgeneration cephalosporins and fluoroquinolones in healthy slaughter pigs might be attributed to the fact that fluoroquinolones are not legally available for food-producing animals in this continent [38]. In 2006/2007, a limited number of 43 E. coli isolates also from healthy swine in Argentina were examined for minimal inhibitory concentration distribution [47].…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, restrictions on live animal imports, geographic isolation, and sound antibiotic stewardship have limited the incorporation and spread of genes encoding resistance to antibiotics used to treat serious human infections among Enterobacteriaceae circulating in food animals (Turner, 2011;Abraham et al, 2015;Reid et al, 2017;Kidsley et al, 2018). Australian porcine Escherichia coli are, albeit at low frequency, known to carry bla CMY−2 , bla CTX−M−14, and bla CTX−M−9 , possibly because of the use of ceftiofur as an off-label, last line antibiotic to treat serious disease (Abraham et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the insertion element IS26 has infiltrated the genomes of commensal E. coli of porcine origin, where it has played a role in altering the genetic context of clinical class 1 integrons and facilitated the acquisition of further resistances (Reid et al, 2017). Furthermore, it is important to identify and characterize the genetic vehicles that can carry class 1 integrons and genes encoding resistance to first generation antibiotics which are widespread in commensal E. coli populations in Australian pigs (Abraham et al, 2015;Reid et al, 2017;Kidsley et al, 2018) because they are likely to acquire genes encoding resistance to clinically relevant antibiotics when resident in commensal enterobacterial populations in the gut of humans and companion animals.…”
Section: Introductionmentioning
confidence: 99%
“…Further review of industry‐based programs will be driven by AMR surveillance. Studies of Australian finisher pigs and a review of AMR identified that E. coli and salmonella bacteria were susceptible to antibiotics that are critically important for human health, indicating that genes determining resistance to critically important antibiotics in these microorganisms are not present or present at a low prevalence in pigs. This proof of concept study provides a baseline for the Australian pork industry and is a good report card.…”
Section: What Does Antimicrobial Stewardship Mean To the Australian Pmentioning
confidence: 99%